A lower blood pressure threshold to define hypertension: the effect on prevalence, control rate, and constituent ratio of systolic and/or diastolic hypertension. Issue 2 (April 2019) - Lai, Min; Zhou, Wei; Wang, Wen-Yin; Wan, Tai-Xuan; Peng, Qiang; Su, Hai
Abstract : Objective: To evaluate the impact of the new US hypertension criteria [systolic blood pressure/diastolic blood pressure (SBP/DBP ≥130/80 mmHg)] on hypertension prevalence and the constituent ratio of three hypertension phenotypes. Participants and methods: This study included 1185 adult participants, who received blood pressure (BP) measurements for 3 days over a 7-day period. At each visit, the BP was measured three times and the average was used as the final value. The criteria of hypertension were if the participant had received treatment with antihypertensive drugs for at least 2 weeks, or SBP/DBP of at least 140/90 mmHg (old criteria) or at least 130/80 mmHg (new criteria) for the untreated participants. The diagnosis of hypertension was made on the basis of first-day BP values (epidemiological method) or the average of the 3-day BP values (clinical method), respectively. The constituent ratios of isolated systolic, isolated diastolic, and systolic–diastolic hypertension were evaluated. Results: When using the old criteria, the overall epidemiological prevalence of hypertension was 41.1% and the overall clinical prevalence of hypertension was 34.8%. When using the new criteria, these values increased to 64.3 and 57.4%, respectively. Meanwhile, against the old criteria, the new criteria increased the constituent ratio of systolic–diastolic hypertension from 24.4 to 50.5% ( P <0.001) for the epidemiological method and from 19.1 to 45.7% ( P <0.001) for the clinical method in the newly diagnosed hypertensive patients. Conclusion: The hypertension criteria of at least 130/80 mmHg not only significantly increased the clinical prevalence of hypertension, but significantly altered the constituent ratio of three hypertension phenotypes among the newly diagnosed hypertensive patients.